Integrated Speed and Driver Fatigue Detected with Method Image Processing - Hadi Pranoto; Andi Adriansyah; Abdi Wahab; Dafit Feriyanto (International Journal of Advanced Technology, 2020)
Integrated Speed and fatigue drivers detected with the image processing method are devices that can give a warning of fatigue when the driver operates a truck or bus, so that potential accidents can be minimized caused by driver fatigue. This device uses the image processing method by image processing with camera right on the driver's face to determine facial changes that include formulated driver yawning intervals in the form of Mount Aspect Ratio (MAR), Eye Aspect Ratio (ER), Eye State (ES), Mouth State (MS), and the Slifa Sleepiness Scale (SSS) is a scale used to describe the driver's sleep level. The results of this research are a device that can detect driver fatigue levels by connecting to speed limiting devices, from the data obtained when range float EAR value less than 0.2 eye close and then value 0.2-0.3 eye condition half open and then greater than 0.3 eye condition open, range float MAR value less than 0.5 mouth close condition, 0,5-0,8 mouth half open and greater than 0.8 mouth open condition, SSS value scale 1-9, if driver condition scale 1-5 fatigue not detected, if the driver scale 6-9 driver fatigue detected.